Promotional Press Releases and Investor Processing Costs - Rawson, Caleb; Twedt, Brady J.; Watkins, Jessica C. (Management Science, 2025)
Press releases are a primary disclosure channel firms use to communicate with investors. However, firms can also use press releases to self-promote to improve their public image. Promotional press releases are, on average, significantly less value relevant than those focused toward investors. They also contain more positive and emotional language as well as less specific and financially oriented language. Based on theories of disclosure processing costs and investor attention, we predict and find that firms’ recent high usage of this disclosure channel to self-promote is associated with increased investor attention and more efficient reactions to subsequent investor-focused disclosures. This effect is concentrated in less visible firms, whereas promotional press releases appear to have no effect on the pricing efficiency of more visible firms. We also provide evidence consistent with media attention being one channel through which these effects operate. Our findings deepen our understanding of how firms use press releases as a disclosure channel and contribute to the literature on disclosure processing costs. This paper was accepted by Eric So, accounting. Funding: This work was supported by resources at the Arkansas High Performance Computing Center. C. Rawson gratefully acknowledges financial support from the Sam M. Walton College of Business. B. J. Twedt gratefully acknowledges financial support from the Mays Business School. J. C. Watkins gratefully acknowledges financial support from the Mendoza College of Business. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.01903 .